2019
DOI: 10.3390/pharmaceutics11110549
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Micro-Pigmentation via Transcutaneous Implantation of Flexible Tissue Interlocking Biodegradable Microneedles

Abstract: Alopecia, characterized by hair follicle blockage and hair loss, disrupts the normal cycle of hair growth. Although not a life-threatening condition, a growing body of evidence suggests that the psychological state of individuals experiencing alopecia can be highly influenced. Despite considerable research on hair loss treatment, interest in micro-pigmentation has increased in recent decades. Micro-pigmentation is an effective method to camouflage the visual contrast between the scalp and hair strands. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…They found that the penetration and efficacy of topical steroid was remarkably higher in the MNAs-treated skin. Lahiji et al [40] also developed a scalp micro-pigmentation approach using BMNAs.…”
Section: Biodegradable Polymersmentioning
confidence: 99%